2011
DOI: 10.1177/1352458510394610
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in multiple sclerosis following subcutaneous interferon beta-1a therapy

Abstract: Background: Women with multiple sclerosis (MS) are advised to discontinue interferon-beta therapy before trying to conceive. Unplanned pregnancies occur and risks related to exposure remain unclear. Methods: To determine pregnancy outcomes following interferon-beta therapy, we examined pregnancies from a global drug safety database containing individual case safety reports received in the post-marketing setting and safety data from clinical trials of subcutaneous interferon beta-1a in MS. Results: One thousand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
72
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 19 publications
9
72
0
5
Order By: Relevance
“…In a recent study, 425 pregnancies had in utero exposure to interferon b with 324 healthy births, 5 congenital abnormalities (4 live births, 1 stillbirth), and 49 spontaneous abortions. 28 A similar pattern was observed in an earlier study in which 41 pregnancies were exposed in utero to interferon b, resulting in 20 healthy offspring, 1 congenital anomaly (hydrocephalus), 1 fetal death, and 8 spontaneous abortions. 29 Two further studies in which in utero exposure to interferon b occurred (n 5 88, n 5 69) reported no significant drug-related congenital defects.…”
Section: (78)supporting
confidence: 55%
“…In a recent study, 425 pregnancies had in utero exposure to interferon b with 324 healthy births, 5 congenital abnormalities (4 live births, 1 stillbirth), and 49 spontaneous abortions. 28 A similar pattern was observed in an earlier study in which 41 pregnancies were exposed in utero to interferon b, resulting in 20 healthy offspring, 1 congenital anomaly (hydrocephalus), 1 fetal death, and 8 spontaneous abortions. 29 Two further studies in which in utero exposure to interferon b occurred (n 5 88, n 5 69) reported no significant drug-related congenital defects.…”
Section: (78)supporting
confidence: 55%
“…This finding may be explained by subclinical levels of circulating AQP4-IgG, which may be present years before clinical presentation. 24,25 The miscarriage rate of 42.9% is outside the 95% CI that would be expected if the true miscarriage rate post-NMOSD was equal to reported rates in multiple sclerosis (expected 95% CI 1.29%-40.9%) 26,27 and just within the expected range calculated from published rates in systemic lupus erythematosus (expected 95% CI 2.56%-45.5%). 28 This suggests that the miscarriage rate in patients with NMOSD is higher than in patients with multiple sclerosis, although larger prospective studies with adequate control groups are needed to test this hypothesis.…”
mentioning
confidence: 65%
“…Boskovic et al [4] showed that the usage of IFNb in the first 3 months of pregnancy caused foetal loss and low birth weight when compared to healthy pregnant control group and unexposed pregnant women with MS. On the contrary, Hellwig et al [17] stated that congenital anomalies were in the normal rate in pregnant women used IFNb and concluded the drug not to have any teratogenic risk. Sandberg-Wollhem et al [40] investigated the teratogenic effects of IFNb-1a on 425 MS patients treated with IFNb-1a in the process of pregnancy by injection under the skin for at least 45 days. They determined 49 spontaneous abortions, 4 stillbirth and 4 children with congenital anomalies; the incidence of spontaneous abortion and congenital anomalies have been noted within normal range.…”
Section: Discussionmentioning
confidence: 99%